Changes in nutrient proteins, inflammatory factors and immunoglobulins before and after enteral nutritional support in patients with cerebral hemorrhage - Tang, Xiaolu; Tan, Wenjun; Li, Xiaoqiang (Journal of Medical Biochemistry, 2025)
Objective: Enteral nutrition support (ENS) is one of the necessary measures after surgical treatment of modern cerebral hemorrhage (CH), and this study will analyze the changes in nutrient proteins, inflammatory factors, and immunoglobulins before and after ENS in patients with CH, which will serve as a reference for future clinics when performing ENS. Methods: 160 ICH patients (76 in the intermittent group and 84 in the continuous group) were included, and changes in indicators before and after EN intervention were retrospectively analyzed in both groups. Including nutrient proteins (albumin ALB, transferrin TRF, prealbumin PAB), inflammatory factors (IL-1β, IL-6, TNF-α), immunoglobulins (IgA, IgG, IgM) and gastrointestinal tolerance. Results: There was no difference in adverse reactions between the two groups during ENS (P>0.05).After ENS, ALB, TRF, PAB, IgA, IgG, and IgM were significantly increased in both groups, while IL-1β, IL-6, and TNF-α were decreased (P<0.05). After ENS, there was no difference in nutrient proteins between the two groups (P>0.05), but inflammatory factors were lower in the intermittent group than in the continuous group, while immunoglobulins were higher than in the intermittent group (P<0.05). Conclusion: ENS constitutes the core mechanism of neuroprotection through a multilayered linkage of “metabolic substrate supply - intestinal barrier repair - immune phenotype remodeling - inflammatory signaling inhibition”.